Incidence, clinical presentation, and antimicrobial resistance trends in Salmonella and Shigella infections from children in Yucatan, Mexico - Zaidi, Mussaret B.; Estrada-Garcia, Teresa; Campos, Freddy D.; Chim, Rodolfo; Arjona, Francisco; León, Magda; Michell, Alba; Chaussabel, Damien (Frontiers in Microbiology, 2013)
Background:Salmonella and Shigella cause significant morbidity and mortality among children worldwide. Increased antimicrobial resistance results in greater burden of disease. Materials and Methods: From 2005 to 2011, Salmonella and Shigella isolates collected from ill children at a major hospital in Yucatan, Mexico, were subjected to serotyping and antimicrobial susceptibility testing by disk diffusion and agar dilution. The identification of blaCTX, blaCMY, blaSHV, blaTEM, and blaOXA and qnr resistance genes was conducted by PCR and sequencing. Results: Among 2344 children with acute gastroenteritis, salmonellosis decreased from 17.7% in 2005 to 11.2% in 2011 (p < 0.001). In contrast, shigellosis increased from 8.3% in 2010 to 12.1% in 2011. Compared to children with Salmonella, those with Shigella had significantly more bloody stools (59 vs 36%, p < 0.001), dehydration (27 vs 15%, p = 0.031), and seizures (11 vs 3%, p = 0.03). In Salmonella (n = 365), there was a significant decrease in resistance to ampicillin (43 to 16%, p < 0.001), trimethoprim–sulfamethoxazole (44 to 26%, p = 0.014), and extended-spectrum cephalosporins (27 to 10%, p = 0.009). Reduced susceptibility to ciprofloxacin in Salmonella rose from 30 to 41% (p < 0.001). All ceftriaxone-resistant isolates harbored the blaCMY-2 gene. qnr genes were found in 42 (36%) of the 117 Salmonella isolates with a ciprofloxacin MIC ≥ 0.125 μg/ml. Four were qnrA1 and 38 were qnrB19. Resistance to ampicillin (40%) and trimethoprim–sulfamethoxazole (58%) was common in Shigella (n = 218), but isolates remained fully susceptible to ceftriaxone and ciprofloxacin. Conclusion: Illness from Salmonella has decreased while severe Shigella infections have increased among children with gastroenteritis in the Yucatan Peninsula. While Shigella resistance to clinically important antibiotics remained unchanged, resistance to most of these, except ciprofloxacin, declined in Salmonella. blaCMY-2 and qnr genes are common in Salmonella isolates.